The book of Al-Itkani al-Farabi on «Ash-Shamil» usul al-fikh: (II part) (Eurasian Journal of Religious Studies, 2017)
This article is about the «ash-Shamil» words (it means «sufficient, full» in kazakh), the author of whichis the well-known sharia scholar, the Kauam ad-din al-Itkani al-Farabi scientist and religious scholar(1286-1357), who released from Kazakh land. This book is known under the name of «Usul al-Bazdaui»,which is the interpretation to the work of Ali ibn Muhammad ibn Al-Husein ibn Abdul Karim ibn Musaibn Isa ibn Mudzhahid al-Bazdaui (400 / 1010 – 482 / 1089) of «Kanz ul usul ila magrifati usul». Thearticle contains the information on the preserved versions of the manuscripts of the works of world libraries,the reason for writing the work: the methodological principles of the scientists are narrated there.